Impeller Submergence Depth for Stirred Tanks - Thiyam Thamphasana Devi; Annu Priya Sinha; Meena Thakre; Bimlesh Kumar (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2011)
Impeller submergence governs the performance of mixing tanks employed in oxygen transfer operation. Present work experimentally investigates the effect of impeller submergence depths on oxygen transfer and corresponding power consumption. It has been found that at higher range of impeller submergence, mixing tanks consume less power and gives higher values of oxygen transfer coefficient. Optimal range of submergence depth is 0.7 to 0.9 times the impeller diameter. © 2011 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)